2021
DOI: 10.18844/wjet.v13i1.5363
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions of content and language integrated pedagogy via electronic communication (e-CLIP)

Abstract: e-CLIP or Content and Language Integrated Pedagogy via Electronic Communication is an innovation in the Thai education system which supports the integration of electronic media and content-based English. e-CLIP is one of the tools developed to cope with the 21st century and has been integrated into several Thai schools in recent years.  This research aims to compare students' perceptions of e-CLIP application in two distinct settings: a small and large-sized school. This study was conducted in Secondary Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…On the platform, students can promptly respond to the various types of questions provided in the interactive slide, and teachers can check the students' answers simultaneously through the teacher dashboard (Sengsri and Anggoro 2021). Teachers can display the answers anonymously on the projector screen while giving verbal feedback (Dong et al 2018).…”
Section: Pear Deck As An Irsmentioning
confidence: 99%
“…On the platform, students can promptly respond to the various types of questions provided in the interactive slide, and teachers can check the students' answers simultaneously through the teacher dashboard (Sengsri and Anggoro 2021). Teachers can display the answers anonymously on the projector screen while giving verbal feedback (Dong et al 2018).…”
Section: Pear Deck As An Irsmentioning
confidence: 99%
“…Since students are hooked on some technological devices such as smart phones and tablets, instructors need to make use of this situation to benefit their learning through a technology-infused version of TGT. As a matter of fact, combining the use of technology with instructions has been found to be effective (Sengsri & Anggoro, 2021). It also has been found that the use of technology such as interactive response systems in English language classrooms improved students' achievement, interest, and self-efficacy (Anak Yunus & Hua, 2021;Anggoro & Pratiwi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Baier et al (2019) found a significant correlation between students' academic performance and teachers' self-confidence in their teaching skills. Sengsri and Anggoro (2021) identified multiple categories of teacher competencies. These tasks involve comprehending students' traits, having knowledge of learning theories, designing lesson plans, nurturing students' innate talents, effectively communicating with students, developing evaluation and assessment techniques, utilizing assessment outcomes, and encouraging reflective learning.…”
mentioning
confidence: 99%